Global existence and asymptotic behaviour for a degenerate diffusive SEIR model - T. Aliziane; M. Langlais (Electronic Journal of Qualitative Theory of Differential Equations, 2005)
In this paper we analyze the global existence and asymptotic behavior of a reaction diffusion system with degenerate diffusion arising in modeling the spatial spread of an epidemic disease.